The Effect Of The Magnıtude And Dırectıon Of The Mastıcatory Muscle Forces And Bıte Force On The Temporomandıbular Joınt Reactıon Force - Nilüfer Darendeliler; Oktay Üner (Galenos Yayinevi, 1998)
The abnormal loads on the temporomandibular joint (TMJ) may lead to degenerative diseases. Orthodontic and orthognathic surgery treatments change the effects of muscle and bite force moment arm on the TMJ. In order to determine these effects, the relations between the bite force, masticatory muscle force and the magnitude and direction of the joint forces are analyzed on a human subject with Class 2 malocclusion and the results are presented graphically. A computer program is developed using the force and moment arm vectors, which results in minimum measurement errors, in equilibrium equations. The effects of masticatory muscles and bite forces are investigated on TMJ reaction force by the developed program.